Friction Stress Analysis of Slag Film in Mold of Medium-Carbon Special Steel Square Billet - Xingjuan Wang; Xulin Si; Liguang Zhu; Tianshuo Wei; Xuelong Zheng (Metals, 2025)
Non-uniform friction and lubrication are the key factors affecting the surface quality of the casting billet. Based on the three-layer structure of the casting powder in the mold, the frictional stress in the mold was calculated and analyzed by using the relationship between the frictional stress and the thickness and viscosity of the liquid slag film, and the lubrication state between the cast billet and the mold was evaluated. Based on the actual production data of 40Mn2 steel and combined with the numerical simulation results of the solidification and shrinkage process of the molten steel in the mold by ANSYS 2022 R1 software, the frictional stress on the cast billet in the mold was calculated. It was found that within the range of 44~300 mm from the meniscus, the friction between the cast billet and the mold was mainly liquid friction, and the friction stress value increased from 0 to 145 KPa. Within 300–720 mm from the meniscus, the billet shell is in direct contact with the mold. The friction between the cast billet and the mold is mainly solid-state friction, and the friction stress value increases from 10.6 KPa to 26.6 KPa. It indicates that the excessive frictional stress inside the mold causes poor lubrication of the cast billet. By reducing the taper of the mold and optimizing the physical and chemical properties of the protective powder, within the range of 44~550 mm from the meniscus, the friction between the cast billet and the mold is mainly liquid friction, and the friction stress value varies within the range of 0–200 Pa. It reduces the frictional stress inside the mold, improves the lubrication between the billet shell and the mold, and completely solves the problem of mesh cracks on the surface of 40Mn2 steel cast billets.